SISTEM PENDETEKSI NOMINAL DAN KEASLIAN UANG KERTAS RUPIAH UNTUK PENYANDANG TUNA NETRA BERBASIS ARDUINO - Ikhsan Ikhsan (JURNAL ILMIAH INFORMATIKA, 2018)
This research refers to some previous research, discussing about computer technology in terms of hardware engineering. The built system is used for the blind in recognizing the nominal and authenticity of the rupiah notes. This study aims to anticipate the rampant circulation of counterfeit money targeting the blind. The method used in the implementation of the system is to use RGB color while the research method is to do literature and laboratory research. The results achieved, utilizing the TCS3200-DB color sensor, can provide an Arduino value to obtain a range of frequencies so that paper money can be identified in nominal value and authenticity. So that the nominal and authenticity of money can be informed via voice via WTV020SD module.